New media of Shanxi ancient architecture tourism development - Zhe, Wang; Alli, Hassan; Md Yusoff, Irwan Syah (Human Resources Management Academic Research Society (HRMARS), 2024)
The heritage has emerged as a vital subcategory within the tourism industry, playing a significant role in the global economic landscape. Shanxi Province, which boasts the highest number of ancient buildings in China, has faced persistent challenges in the development of its tourism sector. This study critically examines the factors contributing to the delayed progress in the tourism of Shanxi's ancient architectural sites. By adopting an interdisciplinary approach, the research delves into the interplay between new media and the promotion of Shanxi's ancient architectural tourism. It analyzes how various forms of new media can be harnessed to overcome existing barriers and stimulate tourism growth. The study culminates in the proposition of a detailed knowledge framework aimed at leveraging new media to enhance the visibility and value of Shanxi Province's cultural tourism. This framework serves as a strategic solution to bolster the province's tourism industry and maximize the economic and cultural benefits derived from its ancient architectural heritage.